Oficina de máquinas: uma maneira de ensinar matemática para alunos do ensino médio - Oliveira Neto, Jayme Alves de (2010)
Currently students are accommodated with the way that they are receiving information, the classes which have a predetermined format being made to theoretical explanation and then is made to exercises whose resolution is closely related to the theory that students should only apply the knowledge acquired and in most cases requires little or no reasoning part of it becoming just a mechanical process. It is proposed to implement a laboratory for teaching mathematics in high schools called " Machinery workshop " which is an initiative to resume in the classroom curiosity and efforts of the student to solve certain problems that are presented in so that necessary degree of mathematical reasoning that enables the resolution. During the execution of the project are worked concepts provided by the teacher and the experiments are conducted and reported by each group with their conclusions. The workshops have been held in a pilot project in a school with high school students from three grades so that the students learn the mechanics of real life. So were prepared classes where students took bicycles, among others, to be studied. At each meeting, each group performed a different activity between virtual activities, constructions with ruler and compass, building mechanisms with industrial materials, analysis of mechanisms of real life. These groups, in each meeting, used their knowledge to the development of a linkage constructed with low cost materials and studied its mathematical properties. The activities were documented on video for analysis and were made audio recordings to allow the transcription of important events thus revealing the strengths and weaknesses of each experiment. We used a camera to capture images during the meetings, and reports of activities carried out by groups with their comments on the meetings and questions that arose. The completion of the project was carried out with an event held at the school where the groups could present their projects developed and show the mechanisms produced by the same to the other students and teachers of the college. The assessment of students is an ongoing process, where the progress of students is perceived in terms of their involvement.